Фітнес-програма для корекції надмірної ваги тіла у жінок - Сергієнко, Юрій Петрович; Крупеня, Світлана Василівна; Чаплигін, Василь Петрович; Овдейчук, Анастасія Олександрівна; Світлана Крупеня; Юрій Сергієнко (Національний педагогічний університет імені М. П. Драгоманова, 2023)
У статті розглядається фітнес програма корекції надмірної маси тіла у жінок першого зрілого віку. Дана проблема є на сьогоднішній день дуже актуальною для жінок першого зрілого віку. Все більше людей мають проблеми з ожирінням та надмірною вагою тіла. Одним з провідних методів корекції маси тіла є фізичні вправи, які, крім зниження надлишкової маси, сприяють також нормалізації обміну речовин, відновленню адаптації організму до фізичних навантажень; нормалізації функцій серцево-судинної та інших систем організму. Для реалізації поставленої мети і завдань нами було на початковому етапі сформовано дві групи по 10 учасниць, які займались в спортивному клубі всі учасниці були першої вікової групи з них 70% мали проблеми з зайвою вагою. Після впровадження програми були отримані позитивні результати у корекції антропометричних показників всіх учасниць. В основу програми увійшли різні фітнес-методики, які використовувались в тижневих навчально-тренувальних заняттях, які тривали вісім тижнів.

The article discusses a fitness program for the correction of overweight in women of early adulthood. This problem is very relevant for women of early adulthood today. More and more people have problems with obesity and overweight. One of the leading methods of body weight correction is physical exercises, which, in addition to reducing excess weight, also contribute to the normalization of metabolism, restoration of the body's adaptation to physical activity; normalization of the functions of the cardiovascular and other body systems, these programs are fitness. Fitness is one of the world's most popular health improvement systems, which allows us to meet the modern needs of different age groups who want to make their figure beautiful and their health strong. The modern fitness industry offers a wide variety of techniques, and these techniques allow to expand the range of effects of physical exercises on the body of those who exercise. We have developed an experimental program, the essence of which is that, taking into account the initial data and individual characteristics of the body constitution of the course participants, physical activity and training volumes were constantly adjusted throughout the program, which gives participants the opportunity to properly approach the training process, learn the basic steps, movements, adapt to the load, try and choose training for their further development, and modern training programs used in the fitness facility help to achieve results in the most To achieve an effective weight loss result, two components must be used: nutritional adjustments and certain fitness training methods. Proper nutrition is an integral part of this process. Dual work improves metabolism and thus metabolic processes in the body, which helps to accelerate the process of reducing body fat. To achieve the goal and objectives, we initially formed two groups of 10 participants who were engaged in a sports club, all of whom were of the first age group, of whom 70% had problems with overweight.
Keywords: жінки першого зрілого віку; розроблена програма; антропометричні дані; зайва вага; фітнес-тренування; women of the first mature age; developed program; anthropometric data; overweight; fitness training